Ethnomathematics comics of Al-Akbar Mosque: Enhancing elementary students' understanding of geometric shapes - Aulia Ika Aulia Oktavia; Via Yustitia; Susilo Hadi; Tommy Tanu Wijaya (UNION : Jurnal Ilmiah Pendidikan Matematika, 2025)
Learning is evolving rapidly in the 21st century, as evidenced by advancements in science and technology (IPTEK), including the use of comics as a medium for learning mathematics. The incorporation of ethnomathematics comics based on the architectural features of Masjid Al-Akbar Surabaya serves as an innovative learning tool to address issues such as unengaging media and students’ reluctance to learn mathematics. This study aims to: (1) examine the process of developing ethnomathematics comics about the Al-Akbar Mosque of Surabaya to help elementary school students recognize the names and characteristics of geometric structures; (2) assess the feasibility of these comics as a learning medium; and (3) analyze teachers' and students' responses to their implementation in the classroom. This study employs a research and development (R&D) approach using the ADDIE development model, which consists of four stages: analysis, design, development, and implementation. Data collection methods include documentation, surveys, observations, interviews, and literature reviews, while data analysis combines qualitative descriptive and quantitative techniques based on expert validation and Likert-scale responses. The results indicate that (1) the three initial stages of the research process—analysis, design, and development—were successfully carried out according to the established framework; (2) validation data from material experts, linguists, and learning media specialists rated the comics as "highly feasible"; and (3) responses from class II-A teachers, expert teachers, and four class II-A students also confirmed a "highly feasible" rating. These findings suggest that the developed ethnomathematics comics based on the Al-Akbar Mosque are effective and appropriate for elementary school students in learning about geometric structures. This research contributes to mathematics education by integrating ethnomathematics into instructional media, fostering cultural appreciation while enhancing students' understanding of geometric concepts. Additionally, it provides a structured framework for developing ethnomathematics-based learning resources that can be adapted to other cultural and architectural contexts.